Thermal Analysis of Solar Air Heater with Ventilator Turbine and Fins - Safitra, Arrad Ghani; Diana, Lohdy; Agil, Denny Muhammad; Fareza, Julfan Hafiz; Arini, Nu Rhahida (EMITTER International Journal of Engineering Technology, 2020)
Solar air heater (SAH) is a renewable energy application for the drying process. SAH has a challenge to produce high performance under uncertain weather. The performance of SAH can be enhanced by providing the absorber plate by adding the fins. This study aims to evaluate the thermal performance of SAH with rectangular fins SAH at low air velocity. This study compares the performance of SAH without fins and SAH with rectangular fins. Two variations of a tilt angle of SAH are 0° and 30° which are observed in this study. The SAH uses a ventilator turbine to suck air into the collector box. The air velocity is 0.01 m/s. The method is experimental. The SAH is tested under real condition from 9 a.m. to 4 p.m. The measurement tools consist of a pyranometer, an anemometer, a temperature sensor in the inlet section, 3 sensors in the absorber plate, a sensor in the outlet section, 6 temperature sensors in the drying cabinet. The result showed the thermal efficiency of SAH with rectangular fins is 29.67 % higher than SAH without fins at 0˚ tilt of angle at noon. The thermal efficiency of SAH with rectangular fins is 25.26 % higher than that of without fins at 30˚ tilt of angle at noon.